MILK CONCENTRATION USING MEMBRANE FOR PARMESAN CHEESE PRODUCTION - Vidiana Phanduwinata, Vira
Parmesan cheese is a type of hard cheese commonly used in Italian dishes such as pasta, pizza, and salad. Parmesan has such unique flavor and aroma of which is developed by the long ripening process. The conventional method of Parmesan cheese production is not efficient enough to attract cheese maker in Indonesia. Therefore, new efficient method to produce Parmesan cheese with less aging time needed and greater cheese yield. In this study, ultrafiltration membrane was used to enhance Parmesan cheese production. The use of ultrafiltration membrane produces milk with less concentration of lactose. Retentate with less lactose is preferable so that there are no excess lactose in the milk due to added NDM (nonfat dry milk). Excess lactose can alter the taste of Parmesan cheese. Ultrafiltration can also reduce the amount of separated whey protein after milk coagulation by rennet. Therefore, there will be greater cheese yield. Specific starter cultures were selected in order to produce Parmesan flavor and aroma without aging time. The aim of this study was to determine the effect of membrane usage, rennet’s amount, final pH of cheese curd, and Parmesan’s final moisture content. Initial procedure was done to determine the optimum condition of milk fermentation. Factors studied in this part are fermenting temperature and each bacteria culture’s concentration. Next, determined optimum condition was used in the next step of producing Parmesan with membrane processing. Factors studied in this part are milk’s concentration factor, rennet’s amount, final pH of cheese curd, and Parmesan’s final moisture content. Determination of the optimum condition was based on protein content test, texture profile analysis, organoleptic test, and yield of the cheese. Optimum condition of milk fermentation are fermenting temperature of 43°C and each bacteria culture’s concentration of 0,1%-v/v. Best Parmesan cheese was made by the following condition: milk concentration factor of 1,18, amount of rennet added 0.015%-v/v, final pH of cheese curd 5.6, and 10% final moisture content.